Expression of Concern to: The α7 nicotine acetylcholine receptor agonist GTS-21 improves bacterial clearance in mice by restoring hyperoxia-compromised macrophage function - Ravikumar A. Sitapara; Daniel J. Antoine; Lokesh Sharma; Vivek S. Patel; Charles R. Ashby; Samir Gorasiya; Huan Yang; Michelle Zur; Lin L. Mantell (BMC, 2020)
The Editors-in-Chief would like to alert readers that this article (Sitapara et al. 2014) is part of an investigation being conducted by the journal following the conclusions of an institutional enquiry at the University of Liverpool with respect to the quantitative mass spectrometry-generated results regarding acetylated and redox-modified HMGB1.